PENGARUH KEPEMIMPINAN ISLAMI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI: STUDI PADA KARYAWAN PT PRIMAYUDHA MANDIRIJAYA - Sari, Putri Arum; Cahyono, Edi (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The company's success can be seen through the performance of its employees, so the company always expects good work from its employees to achieve the goals and standards that have been set.  The aim of the research is to analyze the influence of Islamic leadership on employee performance and organizational commitment as a mediating variable.  This study uses a quantitative approach.  Data were collected by distributing questionnaires using probability sampling, namely simple random sampling of 100 respondents.  Data analysis using the SPSS V.22 application.  The research results show that Islamic leadership partially has a positive and significant effect on organizational commitment, partial Islamic leadership has no effect and is not significant on employee performance, partial organizational commitment has no effect and is not significant on employee performance, organizational commitment is unable to mediate the influence of Islamic leadership on employee performance